2022
DOI: 10.1007/s10265-022-01384-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and morphological analyses of Pilosocereus leucocephalus group s.s. (Cactaceae) reveal new taxonomical implications

Abstract: Pilosocereus is one of the Cactaceae family’s most relevant genera in terms of the number of species and its wide geographical range in the Americas. Within Pilosocereus, five informal taxonomic groups have been recognized, one of which is P. leucocephalus group s.s., whose phylogenetic relationships remain unresolved. Therefore, our objectives are to recognize the circumscriptions of the species in P. leucocephalus group s.s. and to corroborate the monophyly and phylogenetic relationships of this group throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
3
0
2
Order By: Relevance
“…Molecular phylogenetic studies within this clade have suggested the statement of P . leucocephalus s.s. group, although the relationships within this group remain unknown (Franco‐Estrada et al, 2022). Previous phylogenies inferred a closer relationship among non‐Brazilian species and a clade with several northeastern Brazil taxa ( P. glaucochrous , P. pachycladus subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular phylogenetic studies within this clade have suggested the statement of P . leucocephalus s.s. group, although the relationships within this group remain unknown (Franco‐Estrada et al, 2022). Previous phylogenies inferred a closer relationship among non‐Brazilian species and a clade with several northeastern Brazil taxa ( P. glaucochrous , P. pachycladus subsp.…”
Section: Discussionmentioning
confidence: 99%
“…These non-Brazilian species are distributed in North and Central America (P. leucocephalus and P. purpusii), the Antilles (P. polygonus and P. royenii), and the northern Andes (P. lanuginosus) (Figure 3). Molecular phylogenetic studies within this clade have suggested the statement of P. leucocephalus s.s. group, although the relationships within this group remain unknown (Franco-Estrada et al, 2022). Previous phylogenies inferred a closer relationship among non-Brazilian species and a clade with several northeastern Brazil taxa (P. glaucochrous, P. pachycladus subsp.…”
Section: Phylogeny Of Pilosocereusmentioning
confidence: 99%
See 1 more Smart Citation
“…brooksianus se ajustan a la descripción de P. polygonus. El reciente estudio de Franco-Estrada et al (2022) no pudo discriminar los límites entre las especies de Pilosocereus cubanos muestreados, por lo que siguen siendo necesarios estudios adicionales, tanto filogenéticos como morfológicos.…”
Section: Pereskia Mill: Dos Especies [Naturalizadas] (Figura 15)unclassified
“…Dichos tratamientos o inventarios varían entre 29 y 50 taxones nativos, incluidos en 15 -17 géneros (Tabla 1). Pese a que la última década ha sido prolífera en estudios filogenéticos en cactáceas con base en caracteres moleculares donde se han incluido especies cubanas (Hernández-Hernández et al 2011, Majure et al 2013, Franck et al 2013, Korotkova et al 2017, Franco-Estrada et al 2022, Sánchez et al 2022, no siempre los inventarios han considerado las implicaciones taxonómicas y nomenclaturales que dichos estudios han aportortado. También en este periodo han aparecido varios estudios morfológicos que han contribuido a resolver la delimitación entre especies de cactáceas cubanas (Barrios & GonzálezTorres 2015, Franck et al 2019, Lemus-Barrios et al 2021, Barrios et al 2022a.…”
unclassified